Comment by James Turner Johnson - Johnson, James Turner (Journal of religious ethics, 2000)
Comments on: “Just War Theory in Comparative Perspective: AReview Essay” by Simeon O. Ilesanmi Journal of Religious Ethics 28.1 (Spring 2000)